2016
DOI: 10.1097/jcp.0000000000000557
|View full text |Cite
|
Sign up to set email alerts
|

The Validity of the Different Versions of the Hamilton Depression Scale in Separating Remission Rates of Placebo and Antidepressants in Clinical Trials of Major Depression

Abstract: Our objective was to validate the different versions of the Hamilton Depression Scale (HAM-D) both psychometrically (scalability) and clinically in discriminating antidepressants from placebo in terms of remission rates in an 8-week clinical trial in the acute treatment of major depression. The traditional HAM-D17 version was compared with the shorter HAM-D6 and the longer HAM-D21 or HAM-D24 in a fixed-dose placebo-controlled vortioxetine study. Clinical Global Impression of Severity scores were used to establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 17 publications
0
34
0
Order By: Relevance
“…Both Ruhe et al [20] and Kyle et al [21] found that a score <5 on the HAM-D 6 or <8 on the HAM-D 17 was obtained using CGI-S as reference for remission. These remission cut-off scores are important when using remission rates as outcome in treatment studies.…”
Section: Resultsmentioning
confidence: 99%
“…Both Ruhe et al [20] and Kyle et al [21] found that a score <5 on the HAM-D 6 or <8 on the HAM-D 17 was obtained using CGI-S as reference for remission. These remission cut-off scores are important when using remission rates as outcome in treatment studies.…”
Section: Resultsmentioning
confidence: 99%
“…The Major Depressive Disorder Hierarchy PLOS ONE | DOI:10.1371/journal.pone.0170000 January 23,2017patients. This means that they are able to differentiate both the less and the most severe patients in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…This subscale has been called the "melancholia subscale", or HAM-D 6 [21], and has demonstrated that it can meet the criteria for unidimensionality. It is also clinically meaningful, more psychometrically robust, and less likely to mistake side effects of drugs for improvement or worsening in depression [22,23]. Furthermore, even when applied in non-melancholic patients, the HAM-D 6 has shown that it can provide larger effect sizes in clinical trials [24] and even a need for fewer study participants to demonstrate superior antidepressant efficacy [25] in comparison to HDRS-17.…”
Section: Introductionmentioning
confidence: 99%
“…The subscale defined by these six items is now commonly referred to as 'Hamilton-6' (HDRS 6 ) (5). As opposed to the HDRS, the psychometric validity of the HDRS 6 has been confirmed numerous times (8)(9)(10)(11)(12)(13)(14)(15) since its derivation from the HDRS in 1975 (6). Importantly, when using the total score on the HDRS 6 as outcome measure in RCTs of SSRIs (and related antidepressants) versus placebo, the effect sizes are markedly larger than those obtained when using the total score of the HDRS as outcome measure (17)(18)(19)(20).…”
mentioning
confidence: 90%
“…In two landmark studies from 1975 (6) and 1981 (7), respectively, Bech et al demonstrated that the original HDRS met none of these two criteria. This lack of psychometric validity of the HDRS has been confirmed in a large number of studies since then (8)(9)(10)(11)(12)(13)(14)(15). Therefore, the total score of the HDRS cannot be considered as a clinically valid measure of the severity of depression (5,16).…”
mentioning
confidence: 99%